On the free choice of the will, On grace and free choice, and other writings - Augustine, Saint, Bishop of Hippo; King, Peter, 1955- (Cambridge ; New York : Cambridge University Press, 2010)
"The works translated here deal with two major themes in the thinking of St Augustine (354-430): free will and divine grace. On the one hand, free will enables human beings to make their own choices; on the other hand, God's grace is required for these choices to be efficacious. 'On the Free Choice of the Will', 'On Grace and Free Choice', 'On Reprimand and Grace' and 'On the Gift of Perseverance' set out Augustine's theory of human responsibility, and sketch a subtle reconciliation of will and grace. This volume is the first to bring together Augustine's early and later writings on these two themes, in a new translation by Peter King, enabling the reader to see what Augustine regarded as the crowning achievement of his work. The volume also includes a clear and accessible introduction that analyzes Augustine's key philosophical lines of thought"--Provided by publisher.
Machine generated contents note: Introduction; Chronology; Further reading; Note on the texts; List of abbreviations; On the Free Choice of the Will; Reconsiderations, 1.9; Confessions, 8.8.19-8.10.24; Confessions, 7.3.5; On Grace and Free Choice; On Reprimand and Grace; On the Gift of Perseverance, 8.16-13.33; Index of works cited; Index of names and subjects.
Includes bibliographical references and indexes.
Translated from the Latin.
Description based on print version record.
Keywords: Free will and determinism; Grace (Theology); Electronic books